Prinsip Etika Global untuk Kota Modern Multikultural - Togardo Siburian (Societas Dei: Jurnal Agama dan Masyarakat, 2015)
ABSTRACT: This article aims to look at the principles of the idea of global ethics at the implementation of the advanced city in the present day or modern city. The concept of global ethics logically can be considered in a certain local as the common foundations of ethical living in this universal city. Using literature method, the author tries to positively see from the idea of a global ethic associated with globalism, pluralism, secularism, postmodernism, ecumenism and humanitarianism that form the concept of global ethics, which are selectively used to add the principle of good livelihood for the civilization of the world today. The author subsequently tries to see a multidimensional pluralistic city today with a conflict on religious factors, which require a more fundamental principle of unity and universal living. Therefore global ethics is not a substitute for existing religious ethics, but additional ethics for people of different religion without discrimination. So the principle can be implemented at a local anywhere, including major cities in Indonesia.Â KEYWORDS:Â city, modern, crisis, ethics, global, consensus, religions, for all